The Effect of the Implementation of the Problem Based Learning Model on Student Learning Outcomes in Environmental Pollution Material for Class X of SMA Negeri 3 Kisaran in the 2024/2025 Academic Year - Liana Sari Aulya; Tri Harsono (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
Seeing the low student learning outcomes at SMA Negeri 3 Kisaran, it is necessary to select a learning model that can improve student learning outcomes. This study aims to determine the effect of Problem Based Learning on student learning outcomes on Environmental Pollution Material in Class X SMA Negeri 3 Kisaran Academic Year 2024/2025. This study uses a quantitative research method with an ex post facto research type. The research design used is one group pretest-posttest. The research sample was determined through a purposive sampling technique. The research sample consisted of two classes, namely Class X-2 and Class X-4 with the same treatment, namely using the Problem Based Learning model, each class consisting of 36 students. The research instrument was a multiple choice test consisting of 20 validated questions. Data analysis used prerequisite tests and t-tests (paired sample t-test). Based on the results of the data analysis, there was a significant influence on student learning outcomes in the two classes with the same treatment where (sig (2-tailed)) <0.05 where the results obtained were <0.001 <0.005. Based on the hypothesis test, it was found that there was an Effect of the Implementation of the Problem Based Learning model on Student Learning Outcomes in Class X of SMA Negeri 3 Kisaran in the 2024/2025 Academic Year. Thus, the implementation of the Problem Based Learning model was proven to be effective in improving student learning outcomes and was able to foster students' curiosity and thinking skills during the learning process.